2019
DOI: 10.1016/j.tig.2019.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolus and rRNA Gene Chromatin in Early Embryo Development

Abstract: The nucleolus is the largest substructure in the nucleus and forms around the nucleolar organizer regions (NORs), which comprise hundreds of rRNA genes. Recent evidence highlights further functions of the nucleolus that go beyond ribosome biogenesis. Data indicate that the nucleolus acts as a compartment for the location and regulation of repressive genomic domains and, together with the nuclear lamina, represents the hub for the organization of the inactive heterochromatin. In this review, we discuss recent f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 92 publications
1
49
0
Order By: Relevance
“…Classical nucleoli in growing oocytes transform to NPB in fully grown oocyte and disappear during meiotic maturation. Upon fertilization, NPB reappears in both pronuclei of zygotes, gradually disappears, and eventually converts to typical nucleoli with tripartite structure . Because NOP2 is restrictedly localized within the nucleolus and involved in ribosome assembly in yeast, we first examined whether the nucleolar structure was affected upon NOP2 depletion.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Classical nucleoli in growing oocytes transform to NPB in fully grown oocyte and disappear during meiotic maturation. Upon fertilization, NPB reappears in both pronuclei of zygotes, gradually disappears, and eventually converts to typical nucleoli with tripartite structure . Because NOP2 is restrictedly localized within the nucleolus and involved in ribosome assembly in yeast, we first examined whether the nucleolar structure was affected upon NOP2 depletion.…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that the fibrillar center (NPB) plays no role in transcription and active transcription of rDNA occurs in FCs of the nucleolus. 1,33 We found that the ratio of NPB area to the nucleolar area ( Figure 5A,C) was increased and the number of FCs declined ( Figure 5A,D), suggesting a compromised rDNA transcription activity in KD embryos. Altogether, these results showed that NOP2 is a nucleolar protein critically important for the remodeling of nucleolar structure during preimplantation development.…”
Section: Npbs Transformation and Nucleolus Transcription Activitymentioning
confidence: 91%
See 3 more Smart Citations